Gender, religion, and family law : theorizing conflicts between women's rights and cultural traditions - Joffe, Lisa Fishbayn; Neil, Sylvia (Waltham, Mass. : Brandeis University Press, 2012)
"In many regions of the world, rights guaranteed under the civil law, including rights to gender equality within marriage and rights in the distribution of family property and child custody upon divorce, are in conflict with the principles of religious law. Women's rights issues are often at the heart of these tensions, which present pressing challenges for theorists, lawyers, and policymakers. This anthology brings together leading scholars and activists doing innovative work in Jewish law, Muslim law, Christian law, and African customary law. Using examples drawn from a variety of nations and religions, they interrogate the utility of recent theoretical models for engaging with gender and multicultural conflicts, explore contextual differences, and analyze and celebrate stories of successful initiatives that have transformed legal and cultural norms to improve women's lives" --
Introduction : Theorizing conflicts between women's rights and religious laws / Lisa Fishbayn Joffe -- Principles or compromises : accommodating gender equality and religious freedom in multicultural societies / Martha Minow -- Privatizing diversity : a cautionary tale from religious arbitration in family law / Ayelet Shachar -- Marriage pluralism, family law jurisdiction, and sex equality in the United States / Linda C. McClain -- From religious "right" to civil "wrong" : using Israeli tort law to unravel the knots of gender, equality, and Jewish divorce / Susan Weiss -- Flirting with God in Western secular courts : mahr in the west / Pascale Fournier -- Muslim family law in South Africa : conflating the right to religion with the privileging of religion? / Rashida Manjoo -- Recognition of polygamous marriages in the new South Africa / Likhapha Mbatha, Lisa Fishbayn Joffe -- Women, resources, and changing the religious system : a case study of the orthodox Jewish wedding ritual / Irit Koren -- The yoetzet halakhah : avoiding conflict while instituting change / Michal Roness -- The temple of women initiates project : a framework for culturally meaningful feminist expression in rural areas / Fatou Kinø Camara.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Domestic relations; Legal polycentricity; Jews -- Legal status, laws, etc; Muslims -- Legal status, laws, etc; Customary law; Domestic relations -- South Africa; LAW -- Family Law -- General; Customary law; Domestic relations; Jews -- Legal status, laws, etc; Legal polycentricity; Muslims -- Legal status, laws, etc; South Africa; LAW / General; Electronic books